Development of injectable hyaluronic acid/cellulose nanocrystals bionanocomposite hydrogels for tissue engineering applications - Domingues, Rui M. A. (2015)
Injectable hyaluronic acid (HA)-based hydrogels compose a promising class of materials for tissue engineering and regenerative medicine applications. However, their limited mechanical properties restrict the potential range of application. In this study, cellulose nanocrystals (CNCs) were employed as nanofillers in a fully biobased strategy for the production of reinforced HA nanocomposite hydrogels. Herein we report the development of a new class of injectable hydrogels composed of adipic acid dihydrazide-modified HA (ADH-HA) and aldehyde-modified HA (a-HA) reinforced with varying contents of aldehyde-modified CNCs (a-CNCs). The obtained hydrogels were characterized in terms of internal morphology, mechanical properties, swelling, and degradation behavior in the presence of hyaluronidase. Our findings suggest that the incorporation of a-CNCs in the hydrogel resulted in a more organized and compact network structure and led to stiffer hydrogels (maximum storage modulus, Eâ ², of 152.4 kPa for 0.25 wt % a-CNCs content) with improvements of Eâ ² up to 135% in comparison to unfilled hydrogels. In general, increased amounts of a-CNCs led to lower equilibrium swelling ratios and higher resistance to degradation. The biological performance of the developed nanocomposites was assessed toward human adipose derived stem cells (hASCs). HA-CNCs nanocomposite hydrogels exhibited preferential cell supportive properties in in vitro culture conditions due to higher structural integrity and potential interaction of microenvironmental cues with CNCâ s sulfate groups. hASCs encapsulated in HA-CNCs hydrogels demonstrated the ability to spread within the volume of gels and exhibited pronounced proliferative activity. Together, these results demonstrate that the proposed strategy is a valuable toolbox for fine-tuning the structural, biomechanical, and biochemical properties of injectable HA hydrogels, expanding their potential range of application in the biomedical field.